Pregnancy with Non-cirrhotic Portal Hypertension: A Case Report (Journal of Rangpur Medical College, 2024)
Pregnancy with non cirrhotic portal hypertension is an uncommon condition. Due to physiological changes in pregnancy, the patients with portal hypertension may exaggerate and produce life threatening complicationslike variceal haemorrhage and increased incidents of adverse maternal and fetal outcomes. Pregnancy also predisposes the patient to develop hepatic decompensation. So, management of such cases requires a multi-disciplinary approach. In this case report,21-year-old primigravida presented with known case of non cirrhotic portal hypertension at her 33 weeks of pregnancy with huge splenomegaly and history of hematemesis.The pregnancy ran uneventfully, and she underwent elective LSCS at 38+ weeks and gave birth of a live female baby, weighing 3kg was delivered. Post operative recovery was uneventful. The patient was discharged on the 4th post operative day. We want to focus upon different aspects of pregnancy with portal hypertensionto prevent complications and manage the case.J Rang Med Col. March 2024; Vol. 9, No. 1: 86-88